The Use of Multimedia for Learning Badminton - Giri Prayogo; Achmad Sofyan Hanif; Widiastuti Widiastuti (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to develop a multimedia-based learning model of badminton theory and practice. The method used in this research is research and development with 10 steps Borg & Gall. The subjects consisted of 3 experts (badminton, learning, multimedia) and 150 students at three universities that have sports science faculties in West Java. Based on the results of expert validation, the product developed is suitable for use and has been proven to be effective in improving students' badminton skills. Based on the Paired Sample Test, it can be seen that only two Control groups (B and C) have Sig values. (2-Tailed) is more than 0.05 (2-tailed> 0.05) so that in this result it can be stated that Ho is accepted and Ha is rejected, which means that in control groups (B and C) there is no difference in the average initial test scores with the final test. Thus, it can be stated that there is no effect of treatment on improving student badminton learning outcomes. Meanwhile, Pired 1, 4, 5, and 6 (four groups) have Sig values. (2-Tailed) is less than 0.05 (Sig. (2-Tailed) <0.05) so that in this result it can be stated that Ho is rejected and Ha is accepted, which means that there is a difference in the results of the initial test and the final test. Thus, it can be stated that there is an effect of treatment on improving student badminton learning outcomes. Based on the Equal variances assumed section values it is known as Sig. (2-tailed) is 0.039 <0.05, thus Ho is rejected and Ha is accepted, which means that there is a difference in the average test results of the control group and the experimental group. Based on the statistical results of the T test, it can be seen that between the control group and the experimental group there is a significant difference in the results of the final test. This shows that the developed model which was implemented as a treatment for the experimental group, has a better effect than the control group. However, in the control group, of the three groups, there was one group whose paired t test results showed a significant difference between the initial test and the final test. This is something that is beyond the prediction of the researcher, because there are other factors that may influence this achievement outside the variables studied.